Potentials and barriers to land-based mitigation technologies and practices (LMTs) - a review - Karki, Lokendra; Lieu, Jenny; Xylia, Maria; Laub, Moritz; Ismangil, David; Virla, Luis D.; Rahn, Eric; Bilbao, Bibiana Alejandra; Indriani, Siti Nurlaila; Martín Gallego, Pilar; Suleiman, Afnan Khalil Ahmad; Schaldach, Ruediger; et al. (IOP Publishing, 2023)
Abstract Land-based mitigation technologies and practices (LMTs) are critical for achieving the Paris Agreement’s aim of avoiding dangerous climate change by limiting the rise in average global surface temperatures. We developed a detailed two-level classification and analysis of barriers to the adoption and scaling up of LMTs. The review suggests that afforestation/reforestation and forest management are LMTs with wide application and high potential across all continents. BECCS (bio-energy with carbon capture and storage) and biochar have a higher potential in higher-income countries in the short term due to the availability of technology, funding, and existing low-cost biomass value chains. Although most LMTs can be cost-effective across multiple world regions, limited knowledge concerning their implementation and a lack of financing appear to be the main barriers to large-scale deployment. Without considering gender and the rights of marginalised and indigenous communities, the large-scale deployment of LMTs can further aggravate the existing inequalities. Therefore, the social and institutional implications of LMTs also need to be better understood to improve public acceptance and reduce negative impacts. A system approach is necessary to balance the ambitious land-based mitigation targets with the socioeconomic and broader environmental goals.